Dynamics of Islamic Education Curriculum (Concept Analysis, Context and Solutions Efforts) - Darmawan, Herman; Efendy, Arman Noor; Fitri, Muhammad; Cahyadi, Ani (UII Darullughah Waddawah Pasuruan, 2025)
Problems such as the fundamental shift in Islamic education make it necessary for several experts to carry out the latest formulations related to how Islamic education can compete with the times. This research aims to unravel the dynamics of the development of the Islamic religious education curriculum in Indonesia, by analyzing in terms of concepts, contexts and trying to provide solutions as steps for improvement in its development. This study uses literature research with descriptive-descriptive techniques in analyzing the findings. The results show that the Islamic Religious Education Curriculum in Indonesia does have a fairly dynamic process or development. This is related to political factors in the State of Indonesia. It should be a solution effort that may be considered, such as the use of the right strategy, the use of relevant science and technology content, IMTAQ material that is oriented to the teachings of the Prophet, and has a clear typology.